Impact of amendments on soil organic nitrogen fractions irrigated with sodic water - RATHI, DEEPIKA; DEVRAJ, DEVRAJ; ANTIL, R S; SHEORAN, SUNITA (The Indian Journal of Agricultural Sciences, 2020)
Present study was carried out to evaluate the effects of FYM and gypsum on organic nitrogen fractions in soil of long-term field experiment irrigated with sodic water since 1994 at research farm of Department of Vegetable Science, CCS Haryana Agricultural University Hisar, India (2014-2015). Field was irrigated with high RSC (11.5 me/l) sodic water having three levels of gypsum G0 (control), G1 (50 % neutralization of RSC), G2 (100% neutralization of RSC), along with three levels of FYM; F0 (control), F1 (10 tonnes/ha), F2 (20 tonnes/ha). The Results obtained in April 2014 showed that all N fractions (Non hydrolysable-N, NH3-N, amino acid-N, amino sugar-N, hydrolysable unknown-N and total hydrolysable-N) were more dynamic in various treatments consisting FYM and gypsum levels. All nitrogen fractions increased with increasing levels of FYM and gypsum. Averages of amino acid nitrogen, amino sugar nitrogen, ammonia nitrogen and hydrolysable unknown nitrogen constituted about 28-30, 9-12, 27-29 and 29- 36% of total hydrolysable nitrogen, respectively. Adverse effect of residual alkalinity of irrigation water was quite prominent on chemical properties (pH, EC, organic carbon) of soil. The pH of soil was found to be very high under F0G0 and decreased with the use of FYM and gypsum as amendments. This result indicates that the combined use of FYM and gypsum improved soil health and maintained the sustainability of the different vegetable cropping system.